Transformasi Gereja di Era Digital: Kajian Teologis Pra dan Pasca Internet - Agustina Hutagalung; Rencan Carisma Marbun (Pengharapan : Jurnal Pendidikan dan Pemuridan Kristen dan Katolik, 2025)
The development of information technology, particularly the internet and social media, has significantly impacted how the Church functions and interacts with its congregation. This transformation is not only technological but also touches upon fundamental theological aspects. This article aims to examine the changes in the meaning, function, and identity of the Church in the context of digitalization, with a focus on comparing the pre-internet and post-internet eras. Through a systematic theological approach, this analysis explores how the Church, as a community of faith and a spiritual organism, must re-understand its existence amidst the increasingly dominant presence of digital media in believers' lives.In the pre-internet era, church life revolved around physical gatherings, conventional liturgies, and direct spiritual authority. However, in the digital age, new forms of ministry have emerged, such as online worship services, virtual communities, and the dissemination of the Word through social media and other digital platforms. These changes offer opportunities to reach a broader audience but also pose serious challenges such as digital individualism, theological distortion, and a crisis of spiritual authority.This article concludes that the Church needs to develop adaptive ministry strategies while remaining faithful to the essence of Christian spirituality. By maintaining a balance between online and offline ministries and strengthening theological understanding amidst the rapid flow of information, the Church can remain relevant and effective in carrying out its mission.